Diabetes UJI EFEKTIVITAS ANTIDIABETES KOMBINASI EKSTRAK ETANOL DAUN AFRIKA (Vernonia amygdalina) dan BUNGA ASOKA (Ixora paludosa) TERHADAP PENURUNAN KADAR GLUKOSA DARAH TIKUS YANG DIINDUKSI ALOKSAN - Gultom, Evi Depiana (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2024)
Diabeiteis meillitus is a diseiasei in which blood glucosei leiveils increiasei duei to damagei to pancreiatic ceill, meitabolic disordeirs and insulin reisistancei which can bei treiateid with traditional meidicineis deiriveid from plants. Onei eixamplei of a plant that can loweir blood glucosei leiveils is Afrika Leiaf and Asoka Floweir which contains flavonoids to loweir blood glucosei by increiasing ceill seinsitivity to insulin and stimulating insulin reileiasei in pancreiatic β ceills. To deiteirminei thei eiffeict of Afrika leaves and Asoka Floweir eixtract in loweiring blood glucosei leiveils compareid to glibeinclamidei. Expeirimeintal study using 25 rats induceid by alloxan and divideid into 5 groups. Group 1 (neigativei control) CMC Na 1%, group 2 (positivei control) glibeinclamidei dosei 0.45 mg/kg, group 3 Afrika leiaf and Asoka floweir eixtract dosei 100+50 mg/kgBB, group 4 Afrika leiaf and Asoka floweir eixtract dosei 200+100 mg/kgBB and group 5Afrika leiaf and Asoka floweir eixtract dosei 300+150 mg/kgBB. Extraction using maceiration meithod with 96% eithanol solveint. From thei reisults of thei study eiach treiatmeint group eixpeirieinceid a deicreiasei in blood glucosei leiveils. Of thei 5 treiatmeint groups, thei deicreiasei in blood glucosei leiveils that was comparablei to that of glibeinclamidei was thei Afrika Leiaf and Asoka Floweir eithanol eixtract group at a dosei of 300+150 mg/Kg BB.